A century of German psychiatry - Henrik-Peters, Uwe (2001)
The century of German psychiatry between 1899 and 1999 was shaped by creative and catastrophic contrasts. These constrasts and the tensions between them can be personalised by the names of Kraepelin and Freud. During this century there was the unfolding of ideas and many other creative theories and methods of this science in manyfold ways. And also in this time appeared the Nazi psychiatry. In historical perspective not only the murdering of countless psychiatric patients was a disaster. Expulsion, intellectual exhaustion, death of many psychiatrists and war damages too had catastrophic consequences. As a paradox result, German psychiatry -based on the work of the emigrated psychiatrists- got world acknowledgement.